Serosurveillance of Canine Leptospirosis under Different Climatic Conditions in and Around Lahore, Pakistan - Muhammad Hassan Saleem*, Muhammad Sarwar Khan, Muhammad Arif Khan, Muhammad Athar Khan1, Muhammad Ijaz, Ayesha Hassan and Khalid Mehmood (Pakistan Veterinary Journal, 2013)
Leptospirosis is an important zoonotic problem occurring globally. To study the serosurveillance of canine leptospirosis, 429 dogs (265 males; 164 females) blood samples were collected around Lahore city and its peri-urban areas and processed by using canine Leptospira IgG ELISA kit. Of 429 samples, 36.1% were positive serologically for canine leptospirosis. Among 265 male and 164 female dogs, 38.5 and 32.3% male and female dogs were found positive, respectively. Canine leptospirosis was more (38.4%) in adults as compared to pups (27.9%). While season wise serosurveillance was 21.2, 35.8, 40.3 and 49.3% in winter, spring, summer and fall, respectively. It is concluded that highest prevalence of canine leptospirosis is recorded in summer and fall months.